2022
DOI: 10.1093/mnras/stac3177
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating chemically homogeneous evolution in stellar binaries: electromagnetic implications – ionizing photons, SLSN-I, GRB, Ic-BL

Abstract: We investigate the occurrence of rapid-rotation induced chemically homogeneous evolution (CHE) due to strong tides and mass accretion in binaries. To this end, we generalize the relation in Packet (1981) to calculate the minimum angular momentum (AM) accretion required by a secondary star to experience accretion-induced CHE. Contrary to traditionally assumed 5–10 per cent accretion of initial mass (Z ≲ 0.004, M ≳ 20 M⊙) for spinning up the accretor (resulting in CHE) this value can drop to ∼ 2 per cent for eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…Here, M, r g , and v cr are the pre-accretion mass, radius of gyration, and the critical velocity of the star, respectively, and it is assumed that the star is rotating as a solid body. This expression has been adopted from Ghodla et al ( 2023 ), who studied the spin-up efficiency in the secondary component of a binary system due to accretion of mass from a Keplerian disc around the accretor. Since the projection of the VFTS 243 orbit is unknown, we allow all velocities larger than 180 km s −1 (up to critical) in our working.…”
Section: O D E L S a N D N U M E R I C A L M E T H O D Smentioning
confidence: 99%
“…Here, M, r g , and v cr are the pre-accretion mass, radius of gyration, and the critical velocity of the star, respectively, and it is assumed that the star is rotating as a solid body. This expression has been adopted from Ghodla et al ( 2023 ), who studied the spin-up efficiency in the secondary component of a binary system due to accretion of mass from a Keplerian disc around the accretor. Since the projection of the VFTS 243 orbit is unknown, we allow all velocities larger than 180 km s −1 (up to critical) in our working.…”
Section: O D E L S a N D N U M E R I C A L M E T H O D Smentioning
confidence: 99%
“…This makes the CHE pathway of interest as a formation pathway for gravitational-wave sources, as initially suggested independently by and Marchant et al (2016). Since then, several studies have further explored this pathway (de Mink & Mandel 2016; Marchant et al 2017;du Buisson et al 2020;Riley et al 2021;Ghodla et al 2023;Dorozsmai et al 2024). Some studies even suggest that certain observed gravitational-wave sources show significant support for a CHE origin (Qin et al 2022).…”
Section: Introductionmentioning
confidence: 88%
“…CHE has also been considered in the case of very rapidly rotating single stars, where mixing processes resulting from rotation may be responsible for keeping the stars homogeneous (Maeder & Meynet 1987;Yoon et al 2006;Brott et al 2011). In wider binaries, CHE may also occur for the mass-gaining star that is spun up as a result of accretion (e.g., Cantiello et al 2007;de Mink et al 2013;Ghodla et al 2023). In our work, we will refer to these as "birth-spin CHE" and "accretion-induced CHE," respectively, to distinguish them from "tidal CHE" as described in the previous paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the CHE induced by the accretion from its companion could also be reached for massive stars with weak tidal interactions in relatively wide orbits (Cantiello et al 2007). Recently, Ghodla et al (2023) claimed that the accretion-induced CHE could be an important formation channel producing electromagnetic transients like GRBs/Ic-BL (SLSN-I/Ic-BL) 14 under the collapsar (magnetar) scenario. In addition to CEE and SMT, the CHE was also found to play a critical role in contributing to the long GRB rate (Bavera et al 2022c).…”
Section: Properties Of Bbhs Predicted By the Che Channelmentioning
confidence: 99%